Detection of enterotoxin A in coagulase-negative staphylococci isolated from nutrition students - Rojas, Marília Biasetto [UNESP]; Antonelli, Camila Munhoz [UNESP]; Pereira Franchi, Eliane Patricia Lino [UNESP]; da Cunha, Maria de Lourdes Ribeiro de Souza [UNESP] (My University, 2012)
Background: Staphylococcus is a clinically important genus because of its capacity to produce enterotoxins and to cause food poisoning. Staphylococci are the most frequent microorganisms of the skin and mucosal microbiota, with an estimated 20 to 40% of individuals carrying these bacteria on their hands or nose. Since nutrition professionals are involved in the handling and preparation of foods and are possible carriers of these bacteria, the objective of this study was to investigate the presence of Staphylococcus on the hands and in the nasal fossae of undergraduate nutrition students and to determine the enterotoxigenic capacity of these microorganisms. Methods and Findings: A total of 201 strains were isolated from the hands and nose of 61 nutrition students. Of these, 180 (89.5%) were identified as coagulasenegative staphylococci and 21 (10.5%) as S. aureus. Thirty-seven (18.4%) Staphylococcus isolates were producers of enterotoxin A. Toxin production was detected in 5 (19%) of the S. aureus isolates and in 31 (17.2%) of the coagulase-negative staphylococci. Conclusions: This study demonstrated a large number of enterotoxin-producing staphylococci on the hands and nose of nutrition students and professionals involved in the handling and preparations of foods. These findings indicate the need for adequate hygiene measures to prevent food poisoning. © iMedPub.
Keywords: Enterotoxins; Food poisoning; Nutrition; Staphylococcus; Students